2020
DOI: 10.1039/d0tb02242j
|View full text |Cite
|
Sign up to set email alerts
|

Human hair derived uPA loaded capsules with dual near-infrared (I and II biowindows) laser responsive capabilities for multi-effective thrombolysis therapy

Abstract: Problems such as massive hemorrhage caused by uncontrolled drug dosage are the main significant obstacle in clinical thrombolytic therapy, which are prominently due to the lack of targeting and controlled...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…Fang et al showed with their non-theranostic drug delivery system that it is possible however 93 . Here, a light-responsive hair-derived nanoparticle was loaded with urokinase, and encapsulated in gelatin, which melted and released the thrombolytic payload upon heating.…”
Section: Responsive Theranostic Nanocarriersmentioning
confidence: 99%
See 1 more Smart Citation
“…Fang et al showed with their non-theranostic drug delivery system that it is possible however 93 . Here, a light-responsive hair-derived nanoparticle was loaded with urokinase, and encapsulated in gelatin, which melted and released the thrombolytic payload upon heating.…”
Section: Responsive Theranostic Nanocarriersmentioning
confidence: 99%
“…Here, a light-responsive hair-derived nanoparticle was loaded with urokinase, and encapsulated in gelatin, which melted and released the thrombolytic payload upon heating. This resulted in particles with a highly specific release profile, and their in vivo thrombolytic ability could be controlled through NIR radiation 93 . Hence, the adaptation of such a system to also exhibit imaging functionality may result in a highly promising theranostic approach.…”
Section: Responsive Theranostic Nanocarriersmentioning
confidence: 99%
“…Under NIR illumination, photothermal agents or materials can convert light into heat, which can disrupt nanocarriers or their phase transitions, leading to rapid drug release. NIR illumination combined with up-conversion NPs has also been developed. Wang et al developed a NIR-driven nanophotosynthetic biosystem that converts NIR light with excellent tissue penetration ability into visible light via up-conversion NPs to activate oxygen production by Streptococcus elongatus in vivo, enhance angiogenesis, reduce infarct size, and promote brain tissue repair. Thus, the nanophotosynthetic biosystem can improve thrombolytic efficiency, promote angiogenesis, and prevent thrombus recurrence.…”
Section: Nanotherapeutics For Ischemic Strokementioning
confidence: 99%
“…Cancer is responsible for approximately one in six deaths worldwide, which seriously affects the health and quality of life of humans. , Targeted therapy is one of the most convenient treatment options, although it has certain problems, such as poor patient universality and high economic costs. In view of this, patients need to be sorted and treated in the preclinical stage. …”
Section: Introductionmentioning
confidence: 99%